Pengaruh Kepemimpinan Partisipatif dan Disiplin Kerja terhadap Motivasi Kerja yang Dimediasi oleh Kepuasan Kerja pada Badan Perencanaan Pembangunan Daerah Kabupaten Sleman - Ana Suryandari; Arief Subyantoro; Sabihaini Sabihaini (Strata Business Review, 2023)
The achievement of successful regional development managed by the Local Government through the Regional Planning and Development Agency (Bappeda) cannot be separated from professional human resources. They play a very important role in the processes and activities of the Regional Apparatus. Human resources will design, install, operate, and maintain an integral system of the organization. This study aims to determine the influence of participatory leadership and work discipline on work motivation mediated by job satisfaction at the Regional Planning and Development Agency of Sleman Regency. The survey was conducted through the distribution of questionnaires to all civil servants at the Regional Planning and Development Agency of Sleman Regency, a total of 51 respondents. The sampling method used was saturated sampling or census. The data were analyzed using SEM-PLS analysis. The results of the study found that participatory leadership did not have a positive and significant effect on the work motivation of civil servants of the Sleman Regency Bappeda. Work discipline had a positive but insignificant effect on the work motivation of civil servants of the Sleman Regency Bappeda. Job satisfaction did not mediate the influence between participatory leadership and work motivation, and job satisfaction successfully mediated the influence between work discipline and work motivation.